Mortality Burden of Cancer of the Lip, Oral Cavity and Pharynx - Lisbeth Fernández González; José Luis Peñalvo; Armando Humberto Seuc Jo; Delia María Gálvez Medina; Miguel Ángel Martínez Morales; Darilys Losada Gandarilla (Revista Finlay)
Background: an analysis of the trend of change in the mortality of cancer of the lip, oral cavity and pharynx and the quantification of the impact on life expectancy in the Cuban population can help researchers and those responsible for formulating health policies. Public to have a comprehensive view of this problem. Objective: to estimate the mortality burden of cancer of the lip, oral cavity and pharynx, by sex, in Cuba in the period 2005-2020. Method: a descriptive, cross-sectional study was carried out in which five-year data series were used. The universe was made up of all deaths from cancer of the lip, oral cavity and pharynx for the years studied. For each year and causes, the number of deaths was used; rates per 100,000 inhabitants and the years of life potentially lost due to mortality were calculated. The average was calculated and the annual percentage change was estimated. Results: mortality rates were between 7.62 and 12.23 in men and 2.60 and 3.74 in women, per 100,000 inhabitants. Regarding the years of life lost early, due to cancer of the lip, oral cavity and pharynx, it was observed that in men the rates rose from 131 in 2005 to 169 in 2020 and from 40 to 52 in women. Conclusions: the burden of cancer of the lip, oral cavity and pharynx in Cuba has increased, it was higher in men, the trend is growing in both sexes, both men and women died at younger ages due to nasopharyngeal cancer than, due to other locations studied, the percentage change was higher for pharyngeal cancer.